Hubungan Reward Dan Punishment Dengan Motivasi Kerja Perawat Rawat Inap di Rumah Sakit Bakti Timah Karimun - Syahrul Nizam; Rizki Sari Utami; Siska Natalia (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
. Reward and punishment are very important in motivating nurse performance, because through reward and punishment nurses will become more qualified and responsible for the tasks given. This study aims to determine the relationship between reward and punishment and the work motivation of inpatient nurses at Bakti Timah Karimun Hospital. This research uses quantitative research using a correlational descriptive design and a cross-sectional approach. The population in this study were all inpatient nurses at Bakti Timah Karimun Hospital, namely 59 nurses. The sampling technique used total sampling where sample selection was carried out by determining all 59 subjects who met the research criteria. The method used in collecting data was by filling out questionnaires by respondents. Data analysis uses univariate analysis and bivariate analysis. The results of the research show that the reward frequency distribution is mostly in the high category at 54.24%, the frequency of punishment in the high category is 55.93%, the frequency of motivation in the high category of nurses is 50.85%. It is hoped that nurses will increase their knowledge about the applicable reward and punishment system through seminars/socialization in order to increase work motivation and control behavior that can reduce the effectiveness of nurses' performance.